1978
DOI: 10.1002/cber.19781110634
|View full text |Cite
|
Sign up to set email alerts
|

3,4‐Tetramethylen‐1‐phenylpyrrol‐2,5‐diacetonitril

Abstract: born, Chem. Ber. 99, 3444 (1966). Lett. 1969Lett. , 1161

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…2). Flitsch and Kappenberg 16 had reported that such conversions could be done to produce related N-substituted pyrrole-2,5-disubstituted derivatives, either by heating the solid pyrrolidine tautomer or by acid catalysis, but did not give full experimental details. Both methods were examined.…”
Section: Synthesismentioning
confidence: 99%
“…2). Flitsch and Kappenberg 16 had reported that such conversions could be done to produce related N-substituted pyrrole-2,5-disubstituted derivatives, either by heating the solid pyrrolidine tautomer or by acid catalysis, but did not give full experimental details. Both methods were examined.…”
Section: Synthesismentioning
confidence: 99%
“…This species is reasonably presumed to arise via tautomerization of the initial olefination product A to the thermodynamically more stable trisubstituted olefin. Although a few isolated cases of stabilized Wittig olefinations of lactones and esters have appeared in the literature, this condensation is an underutilized reaction in synthetic organic chemistry. Wittig reactions of stabilized ylides with the carbonyl groups of lactones, esters, thioesters, anhydrides, thioanhydrides, amides 17 and imides 18 have been reported in the literature, but many of these systems were intramolecular ring-closure reactions. Attempts to conduct the reaction at lower temperatures (in toluene or xylene at reflux) required longer reaction times and incomplete transformations with poor yields of 4 .…”
mentioning
confidence: 99%
“…[37] and 1,3-diphenyl-4,5-dihydro-4,7-methanoisoindole were used as intermediates for the synthesis of more complicated molecules [38]. 1,3-Di(cyanomethyl)-2-phenyl-4,5,6,7-tetrahydroisoindole [39] was obtained with a yield of up to 0.5% from 2-phenylhexahydrophthalimide and Ph 3 P=CHCN.…”
Section: Other Synthesesmentioning
confidence: 99%